Tornar-se velho: O olhar da mulher homossexual - Lima, Tânia Gonçalves (2006)
This study treats of the representations on the old age and becoming old through the woman's feminine homosexual singular glance in the middle age. The old age feminization is a world phenomenon, present in all of the societies, and the woman homosexual is part of this growing group elder. The investigation with this group of women is presented by the analysis and interpretation of the meanings in the interviewees' speech middle age feminine homosexual. The research seeks to evidence new forms and possible social arrangements for the old age of these homosexual women, which present different family constitution and affectionate relationships from the dominant heterosexual group in the society. The prejudice and the stigma in relation to this minority of women are described and analyzed, evidencing the possibility of a double social prejudice. Reflections about the identity and subjectivity, deviates minority groups, gender and sexuality, family and forms of family organization in the modern society, and the existent relationships among these concepts, also base the theoretical discussion and the analysis of the meanings contained in those women's speeches